A prática regular do futebol: O alto rendimento deste esporte está associado a danos genéticos? - Motta, Marcelo Trotte (2007)
Although physical training has been encouraged as a health-promoting activity, high intensity exercises lead to increased oxidative processes taking place in the mitochondria, thus generating reactive oxygen species, known for inducing DNA damage. This study is aimed at identifying the chromosomal damage in soccer players both during the games and in their physical and technical training programs by means of the Micronucleus Test for lymphocytes following the protocol proposed by Fenech (2000). The sample consisted of three groups: Group I, comprising fifteen soccer players under an intense physical training schedule; Group II, composed of 18 subjects performing physical activities on a regular basis; and Group III with 19 sedentary subjects. The statistical analysis of the number of micronuclei found in the total amount of cells under investigation did not present any significant diferences either in the absolute number of cells with micronuclei or in their mean number: 2=0.3603; G.L.=2; p> 0.70 and F2,,49 = 0.1185; p= 0.8887, respectively. Results in this experiment conditions do not show the potential for micronucleus analysis to biomonitor subjects under intense physical training and point out the need for further studies before this cytogenetic endpoint becomes a risk biomarker.